EKSPLORASI KARANG LUNAK SEBAGAI ANTIOKSIDAN DI PULAU PONGOK, BANGKA SELATAN - Apri, Rezi; Zamani, Neviaty P.; Effendi, Hefni (Jurnal Teknologi Perikanan dan Kelautan, 2017)
Soft coral was a part of reef ecosystem that can produce secondary metabolic compounds, as a response to the environment to survive. The metabolic secundaris one of antioxidant. The purpose of this study to look at the compounds contained in the soft coral Sinularia sp and Lobophytum sp at Pongok Island, South Bangka as antioxidant at a depth of 3 meters and 9 meters. Phytochemical analysis of the study results showed that the soft coral Sinularia sp and Lobophytum sp containing compounds Alkaloids, Flavonoids, Phenols Hydroquinone, Steroids, Triterpenoids, Tannins, and saponin.